Povečanje varnosti mobilne aplikacije v javnem potniškem prometu - Avberšek, Marko (Zbornik mednarodne Elektrotehniške in računalniške konference, 2019)
Security is one of the most important topics in today's development of mobile applications that manage sensitive personal data and financial instruments. Application security must be multi-layered if it is to be successful. When designing the security of the entire system, the mobile application is one of the most vulnerable elements, therefore a high-quality integrated security concept is required from the application's design itself on the phone, to the transfer of data between the application and the backend system, and also the data communication to the terminal equipment in case the applications support it.
Keywords: javni potniški promet; mobilne aplikacije; mobilni operacijski sistemi; šifriranje; Urbana; varnost